A 17‐Year Descriptive Analysis of Firework‐Related Eye Injuries on Territory Day in Northern Australia - Jason R. Daley; Syeda Amel Safi; Ananyaa Devanathan; Jason Lau; Dhanesh Perera; Sandra Brownlea; Zhiqiang Wang; Krishna Tumuluri; Sanditha Wickramasinghe (Emergency Medicine Australasia, 2026)
ABSTRACT Objective Territory Day is celebrated annually on 1st July in the Northern Territory, the only time and place in Australia with unrestricted access to fireworks. While fireworks contribute to the festive atmosphere, they also pose significant risks, particularly to ocular health. This study investigates the incidence, injury types, and outcomes of firework‐related eye injuries on Territory Day for the last 17 years. Methods Retrospective case series of firework‐related eye injuries from 2008 to 2024 presenting to top end hospitals on Territory Day, with 24th July used as a comparison day. Data was collected from electronic and paper‐based medical records. Patient demographics, injury type/mechanism, treatment, and visual outcomes were analysed. Results Forty‐eight cases of firework‐related eye injuries were identified. 77.1% were male, with a mean age of 25.2 years. Eye injuries involved the eyelid/adnexa (58.3%), anterior segment (87.5%) and posterior segment (16.7%). The median ED length of stay was 3.0 h (IQR: 2.0–4.8 h). Posterior segment injuries were seven‐times more likely to be admitted to hospital ( p = 0.024 ). Most injuries (60.4%) occurred in spectators rather than firework operators. 83.3% of injured individuals lacked eye protection. Firework‐related eye injuries accounted for 35.0% (95% CI: 27.0%–43.0%) of all ocular injuries across Territory Days. One hundred and thirty seven ocular injury presentations were recorded on Territory Day, compared with 95 on the comparison day. Conclusions Firework‐related eye injuries represent a preventable cause of ocular morbidity. Public education, appropriate regulation, and community‐based interventions may help reduce the risk of firework‐related ocular injury and support safer celebrations.